Biological aspects of Archaeoprepona demophon muson (Fruhstorfer, 1905) (Lepidoptera: Nymphalidae, Charaxinae) in the Peruvian Amazon - Vásquez Bardales, Joel (2017)
The aim of this study was to elucidate the life cycle of the butterfly Archaeoprepona demophon muson, determine the species of plants to which it relates, characterize its habitat and contribute to the knowledge about their natural enemies. Fieldwork was conducted in two areas near Iquitos (Peru). For the description of the life cycle 20 eggs laid on leaves of it host plant were used. The cycle from egg to adult lasted 85.40 ± 4.66 days under laboratory conditions. The egg period took 5.60 ± 0.52 days. The larva goes through five stages: the first one lasts 8.61 ± 0.77 days; the second 6.12 ± 0.68; the third 11.44 ± 0.73; the fourth 8.13 ± 0.34; and the fifth 27.37 ± 1.29. The prepupa lasted 3.60 ± 0.51 days and the pupa 14.13 ± 2.62; adults were born approximately between 9:00 to 11:00 h. The female lived 41.00 ± 6.35 days and the male 19.25 ± 4.49 days. The host plants were Siparuna bifida (Poepp. & Endl.) A.DC., Pouteria caimito (Ruiz & Pav.) Radlk. and Musa × paradisiaca L. We report two natural enemies, a spider and a fungus.